Patterns of street food purchase in cities from Central Asia (vol 9, 925771, 2022) [correction] - Sousa, S (2022)
In the published article, there was an error in Figure 5 as published. The legend for the red bars was Industrial only and the legend for the green bars was Homemade and industrial.However, these legends weremistakenly switched. As such, the correct legend for the red bars is Homemade and industrial and the correct legend for the green bars is Industrial only. The corrected Figure 5 and its caption appear below. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. (c) 2022 Sousa, Lança de Morais,Albuquerque, Gelormini, Casal, Pinho, Motta, Damasceno, Moreira, Breda, Lunet and Padrão.